Evaluation of bioprinted autologous cartilage grafts in an immunocompetent rabbit model [data] - Gvaramia, David; Fisch, Philipp; Flégeau, Killian; Huber, Lena; Kern, Johann; Jakob, Yvonne; Hirsch, Daniela; Rotter, Nicole (Universität, 2024)
The current gold standard of auricular reconstruction involves a highly time-consuming manual graft assembly from autologous costal cartilage. The intervention may require multiple surgical procedures and lead to donor-site morbidity, while the outcome is highly dependent on individual surgical skills. A tissue engineering approach provides the means to produce cartilage grafts of a defined shape from autologous chondrocytes. The use of autologous cells minimizes the risk of host immune response; however, factors such as biomaterial compatibility and in vitro maturation of the tissue-engineered (TE) cartilage may influence the engraftment and shape-stability of TE implants. Here we tested the biocompatibility of bioprinted cartilage constructs containing autologous auricular chondrocytes in a rabbit model. The TE cartilage was produced by embedding autologous auricular chondrocytes into hyaluronan transglutaminase (HATG)-based bioink, previously shown to support chondrogenesis in human auricular chondrocytes in vitro and in immunocompromised xenotransplantation models in vivo. While the shape of the transplants was overall retained, drastic softening and loss of cartilage markers, such as sulfated glycosaminoglycans and collagen type II were observed. Furthermore, fibrous encapsulation and partial degradation of the transplanted constructs were indicative of a strong host immune response to the autologous TE cartilage. The current study thus illustrates the crucial importance of immunocompetent autologous animal models for the evaluation of TE cartilage function and compatibility.
Gesehen am 11.03.2024
Gefördert durch: Swiss National Science Foundation: CRSII5_173868
Keywords: Forschungsdaten; Datenbank